Pattern of Contraceptive Use among the Married Couple of Rural Community in Cumilla District (Central Medical College Journal, 2022)
Background: Bangladesh has experienced a sevenfold increase in its contraceptive prevalence rate (CPR) in less than forty years from 8% in 1975 to 62% in 2014.Contraceptive practice acceptable moderately in society is said to be associated with socio-economic status, education and other factors. Population stabilization and a gradual lowering of population growth is the basic aim behind contraceptive practice. The population rate of Bangladesh in December, 2018 was 2.01%. The population density is 1252 per km2. Maximum of the population increased in the rural area, because they were not properly used the contraceptive methods. They seldom used contraceptive methods which influenced to increase the population. The purpose of the study is to examine the pattern of contraceptive use among the married couples of the rural area in Bangladesh. The objectives of the study is to determine the extent of awareness regarding contraception among the married persons, to estimate the perception of couples using contraceptive methods, identify the reasons for their adoption & non-adoption and to assess needs of contraceptive methods in rural area. Materials andMethods: It was a descriptive type of cross sectional study, which was carried out in some selected villages at Laksham, Cumilla. Study populations were married women in reproductive age and married man. Purposive sampling was done. Sample size was 333. The number was identified on the basis of assumption. Pretested questionnaire and checklist were used for data collection.Result: It was found that the age range of the respondents were 16 to 70 years, among the 333 respondents 34.2%were 20 to 29 years of age group, 86% were female &14% male.42.6% respondents were educated up to primary level. Majority of the respondents had 10,000 to 20,000 monthly family income. Among 333 respondents majority 28.5% had 3 children. 65.46% of the respondents were house wife, 80.5% respondents were using different types of contraceptive methods, 62.5% were using OCP, 3% IUCD, 3.9% barrier method or condom, 1.5% were in terminal method. 46.8% discontinue their previous contraceptive methods, 11.1% suffered from irregular period and 5.1% weight gain. 68.5% respondents were satisfied with their current contraceptive method, 36% felt need to adopt the contraceptive methods, 18.6% motivated by health workers, 25.2% influenced by the family members and 0.9% by the media. The number of children directly dependent on the educational qualification and monthly family income and are statistically significant (at p